The Application of Body Rhythm in Music Therapy - Taking the Experience of Autistic Children as An Example - Zhang, Yuchi (Journal of Theory and Practice of Social Science, 2024)
According to the data of 2021, the number of autistic people in China exceeds 10 million, and the number of autistic children exceeds 2 million. However, there is no specialisation in autism rehabilitation and intervention in the domestic education system, and most practitioners receive training only after joining the profession. In the new period of the "14th Five-Year Plan", the state has put forward new guidance for the development of the autism industry, and the number of special education institutions and practitioners has increased rapidly, but at the same time, they are also facing the bottleneck of the application of diversified methods of rehabilitation therapy, and the insufficient construction of the accreditation system and standardisation, and other problems. Based on the concept of music therapy and the scientific theories required for the rehabilitation of children with special needs, the study explores the integration of the role of music and rehabilitation interventions, combining musical elements with the practice of somatic rhythms, and paving the way for medical rehabilitation after long-term planned training, promoting physical coordination, exercising imitation and observation skills. The assessment system for the application of body movement derived from the practice is summarised to provide reference for the service model and future development of children with special needs.